Pengaruh Pengetahuan Ibu dan Dukungan Suami terhadap Adaptasi Perubahan Psikologis Ibu Hamil Primigravida Trimester I di PMB (Praktik Mandiri Bidan) Cisalak Pasar, Cimanggis, Depok Tahun 2020 - Rina Wijayanti (Maternal & Neonatal Health Journal, 2021)
In her life a woman will experience sensitive times that is when pregnancy is present, because at that time women will become vulnerable to the onset of physical and mental disorders. The support of the husband during pregnancy, childbirth and postpartum is indispensable. The purpose of this study is to know the influence of knowledge and support of husbands on the adaptation of psychological changes primigravida trimester I. The type of research used is quantitative research with a cross sectional approach. The population used by all Trimester I pregnant women who conducted the examination period January - June 2020 in The Independent Practice of Midwives Cisalak Village Market District Cimanggis - Depok, using accidental sampling. The instrument used is quesionnaire. The results of the study there is an influence of knowledge on the adaptation of psychological changes Primigravida Trimester I pregnant women with p value = 0.001, and OR = 7,547 (2,402 – 23,708) and there is an influence of husband support on the adaptation of psychological changes primigravida Trimester I with p value = 0.000, and OR = 15,536 (3,114–77,519).